The impact of Esg factors on financial performance in the European energy sector - Meireles, M.; Falcão, L.; Robaina, M.; Madaleno, M. (2025 21st International Conference on the European Energy Market (EEM), 2025)
The European energy sector is crucial in promoting sustainable economic growth but faces increased pressure to adhere to environmental, social, and governance (ESG) standards. ESG adoption is no longer a matter of compliance only but a way of significantly influencing companies' financial performance and strategic positioning. Indeed, integrating ESG factors significantly impacts public perception and is increasingly recognized as a key determinant of financial performance. Therefore, this study investigates how ESG factors, individually and collectively, influence the financial performance of European energy companies and which specific ESG practices contribute most to financial resilience and profitability. Furthermore, it studies how varying regulatory frameworks and market conditions shape the relationship between ESG adoption and financial performance in compliance with Sustainable Development Goals (SDGs). The study concludes that adopting robust ESG practices enhances the financial resilience of European energy companies, demonstrating that sustainability efforts may not be aligned with profitability. Also, governance measures were revealed to have the most substantial effect on financial performance and leverage.